La categoria gramatical del temps i les relacions deíctiques i anafòriques - Pérez Saldanya, Manuel (Caplletra. Revista Internacional de Filologia, 2015)
This paper discusses the distinction between absolute and relative tenses (or between deictic and anaphoric tenses) and suggests that the absolute tenses have got a complex temporal interpretation at the level of the Logical Form. In this interpretation there are two different temporal elements involved, one of which functions as a pronominal and follows Principle B of the Bounding Theory.